Case report: Catheter ablation for persistent atrial fibrillation in a patient with heart of stone - Deng, Yingjian; Li, Guiyang; Liu, Jianghai; Wan, Xingcai; Li, Linlin; Lv, Jialan; Li, Qiang; Zhou, Faguang; Chang, Dong (Frontiers in Cardiovascular Medicine, 2023)
Myocardial calcification is a rare condition, with only a few reports in the literature. For the first time, we report a case of diffuse myocardial calcification who underwent successful catheter ablation for persistent atrial fibrillation (AF). In this case, catheter ablation was recommended due to repeated hospitalization for palpitation and heart failure, but preoperative computed tomography showed massive myocardial calcification. Electroanatomic mapping of the atrium was performed with a Pentaray catheter before ablation, which showed areas of low voltage in the calcified region. As the persistent AF was terminated after circumferential pulmonary vein isolation and posterior wall isolation, and no further ablation was performed. The patient recovered well, with no recurrence of palpitation or heart failure during the one-year follow-up.